1994
DOI: 10.1289/ehp.94102s1109
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity of dose-response functions for carcinogenicity.

Abstract: Carcinogenesis data for 315 chemicals were obtained from the National Cancer Institute-National Toxicology Program (NCI-NTP) bioassay programs and were analyzed to examine the shape ofcarcinogenesis dose-response curves. Tumor site data were more often consistent with a quadratic response than with a linear response, suggesting that the routine use of linear dose-response models will often overestimate risk. Information from in vivo short-term mutagenicity and genotoxicity assays was also obtained for most oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In fact, examination of the shape of carcinogenesis dose-response curves of 315 chemicals tested in the National Cancer Institute-National Toxicology Program revealed that data were more often consistent with a quadratic response than with a linear response. Also, genotoxic compounds differed from linearity more often than non-genotoxic compounds (Hoel & Portier 1994).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, examination of the shape of carcinogenesis dose-response curves of 315 chemicals tested in the National Cancer Institute-National Toxicology Program revealed that data were more often consistent with a quadratic response than with a linear response. Also, genotoxic compounds differed from linearity more often than non-genotoxic compounds (Hoel & Portier 1994).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the proportion positive only at the high dose is similar for mutagens and nonmutagens (Gold et al., unpublished data). Another analysis of the shape of dose response curves indicates that a quadratic dose response is compatible with more of the data than a linear one for both mutagens and nonmutagens (115). That mitogenesis at neartoxic doses is important in the carcinogenic response at the MTD is also suggested by the lack of chemicals that are highly carcinogenic relative to their MTD.…”
Section: Dna Repair and Other Inducible Defensesmentioning
confidence: 88%
“…Without the two extreme cohorts the range becomes 0.89-2.0 with a central estimate of 1.4. No previous analysis of the epidemiological data has suggested a concave relationship, though experimental data for a wide range of carcinogens (Hoel and Portier, 1995) suggest they may be quite common. Across the range of exposures in a single study, and given the uncertainties in individual exposure estimation, a moderate degree of non-linearity will be difficult to detect.…”
Section: Lung Cancermentioning
confidence: 99%